國小中高年級國語文教材事理類說明文學習內涵之探究Exploration of Reasoning Exposition-Oriented Content in Chinese Teaching Material for the 3rd to 6th Graders - 陳佳宜Chia-Yi Chen; 楊淑華Shu-Hua Yang; 黃慧文Hui-Wen Huang (Higher Education Foundation, 2008)
本研究以國小中、高年級國語文之說明文教材為研究文本，歸納探討當中之事理類說明文的教材類型及分布現況，接著以「事理類說明文教材檢視表」，針對國語課本、教師手冊及習作，檢視後進行分析，以瞭解現行三家版本事理類說明文教材，作為未來編撰修改之基礎。研究發現，說明文題材大致符合學生的生活經驗，但文體分類與界定不夠明確、教材選編比例偏低、不同類型說明文教材分布差異大，而事理類說明文教材編寫缺乏層次性、寫作及文體特徵相關題型未能完整規劃，導致教學重點容易被忽略。最後，根據研究結果引申出針對教材、教學及未來研究的建議，以充實事理類說明文教材內容。 This study is based on the teaching materials of exposition in Mandarin textbook of three versions as the basis of study. First, generalize and treat the teaching materials and distribution of the reasoning exposition in Mandarin textbooks in grade 3-6 curriculum. Then accumulate the opinions of elementary school teachers by "checklist of the reasoning exposition" to inspect the materials, teacher's manuals and workbooks. After that, analyze the content of the reasoning exposition of three versions and give advice to further editions. From the study, it is found that the subject arrangement of the exposition accords with the experience of the pupils approximately, the discrimination in the literary form is not explicit enough, the proportion of the exposition in the textbooks is low, the distribution and proportion of different type of expositions in three versions differs from each other very much, the composition of content is lack of the arrangement of ideas, the exercises of writing and expository feature are not well integrated. Therefore, based upon the findings of this study, the main point of the reasoning exposition is usually neglected. Finally, in order to enrich the content of the reasoning exposition, suggestions founded on the results of the study were indicated to the material, real teaching of teachers and the researches in the future.